Multi-country evaluation of the sensitivity and specificity of two commercially-available NS1 ELISA assays for dengue diagnosis - Guzmán, María G.; Jänisch, Thomas; Gaczkowski, Roger; Hang, Vo Thi Ty; Sekaran, Shamala Devi; Kroeger, Axel; Vazquez, Susana; Ruiz, Didye; Martinez, Eric; Mercado, Juan C.; Balmaseda, Angel; Harris, Eva; et al. (PLoS neglected tropical diseases, 2010)
Background Early diagnosis of dengue can assist patient triage and management and prevent unnecessary treatments and interventions. Commercially available assays that detect the dengue virus protein NS1 in the plasma/serum of patients offers the possibility of early and rapid diagnosis. Methodology/Principal Findings The sensitivity and specificity of the Pan-E Dengue Early ELISA and the Platelia™ Dengue NS1 Ag assays were compared against a reference diagnosis in 1385 patients in 6 countries in Asia and the Americas. Platelia was more sensitive (66%) than Pan-E (52%) in confirmed dengue cases. Sensitivity varied by geographic region, with both assays generally being more sensitive in patients from SE Asia than the Americas. Both kits were more sensitive for specimens collected within the first few days of illness onset relative to later time points. Pan-E and Platelia were both 100% specific in febrile patients without evidence of acute dengue. In patients with other confirmed diagnoses and healthy blood donors, Platelia was more specific (100%) than Pan-E (90%). For Platelia, when either the NS1 test or the IgM test on the acute sample was positive, the sensitivity versus the reference result was 82% in samples collected in the first four days of fever. NS1 sensitivity was not associated to disease severity (DF or DHF) in the Platelia test, whereas a trend for higher sensitivity in DHF cases was seen in the Pan-E test (however combined with lower overall sensitivity). Conclusions/Significance Collectively, this multi-country study suggests that the best performing NS1 assay (Platelia) had moderate sensitivity (median 64%, range 34-76%) and high specificity (100%) for the diagnosis of dengue. The poor sensitivity of the evaluated assays in some geographical regions suggests further assessments are needed. The combination of NS1 and IgM detection in samples collected in the first few days of fever increased the overall dengue diagnostic sensitivity.
Gesehen am 05.06.2023